PENATAAN AREA SLUM PEDAGANG IKAN BASAH PANTAI PASIR PANJANG SEBAGAI OBJEK WISATA PESISIR DAN KULINER KOTA KUPANG - Robin Tibuludji; Jasinta Dessy Tapatfeto; Rosdiana Matta (PROGRAM STUDI AKUNTANSI - UNIVERSITAS MUHAMMADIYAH KUPANG, 2018)
Pasir Panjang beach area along the front of Aston Hotel in the last dozen year has been covered by emergency and slum wet fish seller stalls. Coastal areas becoming waste disposal and fish-cut waste. Seeing the conditions and developments, it is necessary to rearrange the region. The research method is an environmental assessment using SWOT analysis, economic development, and spatial analysis. The ultimate goal of this research is to restore Pasir Panjang beach as a comfortable recreational environment for the community, as object of coastal and culinary tourism in Kupang city, as well as improving economy and quality of wet fish traders and local people. The results showed that the quality of life of the coastal community of Kelapa Lima has begun to improve according to 7 (seven) indicators of Organization of Economic and Culture Development (OECD); coastal communities have not been too aware of the importance of maintaining environmental quality; the government needs to provide a special space for various socioeconomic activities of the population including the need for open sight view; policy development of socio-economic and environmental structure had to put into a Master-plan.